Time Is Money: The Effect of Mode-of-Thought on Financial Decision-Making - Krava, Lidor; Ayal, Shahar; Hochman, Guy (Frontiers in Psychology, 2021)
The dual-system approach holds that deliberative decisions and in-depth evaluation processes lead people to better financial decisions. However, research identifies situations where optimal economic decisions may stem from a more intuitive decision process. In the current work, we present three experimental studies that examined how these two modes of thought affect financial decisions. In Study 1, deliberative processes were indeed associated with better one-shot descriptive-based financial decisions. However, Study 2 showed that when participants were asked to make repeated decisions and were required to learn from their experience, the advantage of deliberative over intuitive processes was eliminated. In addition, when participants employed intuitive processes, the quality of their financial decisions improved significantly with experience. Finally, study 3 showed that the deliberative processing style may lose its advantage when information is not fully available. Overall, these findings suggest that deliberation may contribute to financial decision-making in one-shot decisions. However, when information is lacking, and decisions are repetitive, intuitive processes might be just as good.